Relationship between teachers’ professional identity and career satisfaction among college teachers: role of career calling - Wu, Jinshun; Ghayas, Saba; Aziz, Aiman; Adil, Adnan; Niazi, Sadia (Frontiers in Psychology, 2024)
Objectives Professional identity has been found an important determinant of career satisfaction of employees working in various fields. Teachers’ professional identity is a relatively less explored domain. Considering the importance of teacher’s career satisfaction, the current study was designed to test the role of career calling in the relationship between teachers’ professional identity and career satisfaction. Methods A sample of teachers (N = 300) with (n = 115) men and (n = 185) women was recruited from the colleges of Sargodha City, Pakistan with an age range from 24 to 45 (M = 31.3, SD = 6.4). A purposive sampling technique was employed for data collection. Variables of the present study were operationalized through the Professional Identity Scale, Brief Calling Scale, and Career Satisfaction Scale. Results Path analysis revealed that normative identity did not have any direct or indirect effects on career satisfaction and career calling. Whereas affective and efficacy identity demonstrated significant positive direct effects on career calling whereas career calling had significant positive direct effect on career satisfaction. Efficacy identity also had a significant positive direct effect on career satisfaction. Finally, both affective and efficacy identity had significant positive indirect effects on career satisfaction via career calling. Conclusion The findings of the current study may help in devising plans to improve the career satisfaction of teachers working in the higher education sector.